2010
DOI: 10.1007/s00068-010-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived circulating free DNA (cf-DNA/NETs), a potential prognostic marker for mortality in patients with severe burn injury

Abstract: The predictive value of circulating free DNA/neutrophil extracellular traps (cf-DNA/NETs) has recently been shown in patients with major trauma for sepsis, multiple organ failure, and mortality. Here we report on the predictive potential of cf-DNA/NETs for mortality in patients with severe burn injury. In a prospective study 32 patients with severe burn injury were included. Blood samples were sequentially obtained on day 1, 3, 5, and 7 after admission. cf-DNA/NETs was directly quantified from plasma by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 36 publications
2
56
0
1
Order By: Relevance
“…The ROC-curve analysis, which combines sensitivity and specificity of a test, showed a better predictive value, with a larger area under the curve and smaller 95% confidence intervals, than obtained with the cf-DNA/NETs marker: 0.93 (0.84-1.00) vs. 0.85 (0.68-1.00); but as seen in the article of Altrichter, even the 30y old ABSI model appeared to be notably better than the DNA marker with especially a higher specificity and positive predictive value (respectively 92% and 75% for the ABSI model vs. 76% and 46% for the cf-DNA/NETs marker). Therefore, we agree with the authors, that a single parameter such as the cf-DNA/NETs marker should never be used as only predictor of mortality [1].…”
Section: Dear Editorsupporting
confidence: 90%
See 3 more Smart Citations
“…The ROC-curve analysis, which combines sensitivity and specificity of a test, showed a better predictive value, with a larger area under the curve and smaller 95% confidence intervals, than obtained with the cf-DNA/NETs marker: 0.93 (0.84-1.00) vs. 0.85 (0.68-1.00); but as seen in the article of Altrichter, even the 30y old ABSI model appeared to be notably better than the DNA marker with especially a higher specificity and positive predictive value (respectively 92% and 75% for the ABSI model vs. 76% and 46% for the cf-DNA/NETs marker). Therefore, we agree with the authors, that a single parameter such as the cf-DNA/NETs marker should never be used as only predictor of mortality [1].…”
Section: Dear Editorsupporting
confidence: 90%
“…These extracellulary DNA structures (produced by neutrophils as defense mechanism trapping and killing pathogens) have previously shown to predict sepsis and mortality in multi-trauma patients [1]. In outcome prediction, mortality is the most objective endpoint, although sepsis and multi-organ failure are also important endpoints [2,3].…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…However, quantification of NETs in vivo is more difficult than expected because NETs are an extracellular fibrous component, which is difficult to measure precisely by commonly used experimental techniques such as Western blotting, ELISA, PCR, or flow cytometry. Some studies have reported on using the quantity of circulating free DNA to estimate the quantity of NETs in serum [18,19]. However, it is uncertain whether circulating free DNA reflects the amount of NETs directly.…”
Section: Discussionmentioning
confidence: 99%